2019
DOI: 10.1016/j.mrgentox.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The response of Escherichia coli to the alkylating agents chloroacetaldehyde and styrene oxide

Abstract: DNA damage is ubiquitous and can arise from endogenous or exogenous sources. DNA-damaging alkylating agents are present in environmental toxicants as well as in cancer chemotherapy drugs and are a constant threat, which can lead to mutations or cell death. All organisms have multiple DNA repair and DNA damage tolerance pathways to resist the potentially negative effects of exposure to alkylating agents. In bacteria, many of the genes in these pathways are regulated as part of the SOS reponse or the adaptive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Prior work showed that symE is under LexA control, and it was shown early on to be DNA damage‐inducible (receiving the designation of dinL ) and part of the SOS regulon (Fernandez De Henestrosa et al., 2000; Lewis et al., 1994). One recent study found that a ΔsymER strain has a modest growth defect after treatment with the alkylating agent styrene oxide (Muenter et al., 2019), but symE is not required to survive other DNA damaging agents such as mitomycin C (Kawano et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work showed that symE is under LexA control, and it was shown early on to be DNA damage‐inducible (receiving the designation of dinL ) and part of the SOS regulon (Fernandez De Henestrosa et al., 2000; Lewis et al., 1994). One recent study found that a ΔsymER strain has a modest growth defect after treatment with the alkylating agent styrene oxide (Muenter et al., 2019), but symE is not required to survive other DNA damaging agents such as mitomycin C (Kawano et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Though induced in the SOS response, there is limited evidence of a role for SymE in recovery from DNA damage. Δ symE mutants show no growth difference in most DNA damaging conditions except for a modest defect when treated with styrene oxide (Kawano et al., 2007; Muenter et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The differences in expression levels were obvious for E. coli treated with different SUC concentrations. In this study, a TELI value of 1.5 was set as the toxicity limit, with TELI > 1.5 considered to be significantly toxic, in line with previous literature (Hayes and Dalton, 2015;Muenter et al, 2019).…”
Section: Transcriptional Effect Level Index Assaymentioning
confidence: 90%
“…The TELI analysis has been used for characterizing specific functional-impairment stress in cells exposed to different drug concentrations (Gou et al, 2014;Hayes and Dalton, 2015). Therefore, this analysis provides information on the number and identity of genes with altered expression, the magnitude of the alteration, and the temporal pattern of gene expression change in response to toxicant exposure (Muenter et al, 2019). Furthermore, cellular responses of SUC after different disinfection processes were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Traces of microplastic components have been found in potable water, food sources and air, and are associated with elevated risk of a number of diseases including cancer ( 2 ). Bisphenol A (BPA) and styrene-7,8-oxide (SO) are common compounds used in the production of epoxy resins and polycarbonate plastics ( 3 , 4 ). They are also major components of microplastic waste globally, and have recently been included in the list of carcinogens by the World Health Organization's International Agency for Research on Cancer.…”
Section: Introductionmentioning
confidence: 99%